Immunogenicity of soluble enterovirus 71 recombinant VP1 protein in mice model - Mustafa, Suhaili (2017)
Enterovirus 71 (EV71) is one of the causative agents of the hand, foot and mouth disease (HFMD) in human. Outbreaks of HFMD may lead to severe pathogenesis in young children and infants worldwide. Children below 5 years of age are more susceptible to severe forms of HFMD which are associated with neurological complications. In adults, EV71 infections are mild and uneventful. Despite the threat to children worldwide, there is still no effective vaccine available that can really prevent this disease. Development of an effective vaccine towards EV71 infection is obstructed by the lack of suitable candidates. To date, various type of candidate vaccines are being studied and evaluated. They include inactivated whole-viruses, attenuated viruses, virus-like particles, subunit proteins, and DNA vaccines. However, the most promising of them are in the form of inactivated whole virus. The risk of using the inactivated whole virus as a vaccine is a potential for incomplete inactivation, resulting in the vaccinee receiving live virulent virus. To address this issue, alternative vaccine candidates have been developed. They include subunit viral proteins that served as the immunogens. Viral protein 1 (VP1), the capsid protein of EV71, has a higher degree of antigenicity compared to its other structural proteins. It also serves as a major viral neutralization determinant. These properties of VP1 have made it an ideal target in the development of EV71 vaccine. It is located in its C-terminal region. Therefore, peptides corresponding to these regions will be ideal candidates for EV71 vaccine development. In the present study a recombinant construct of NPt-VP1198-297 (NPt-VP1t) were cloned and expressed in E. coli systems. The protein was expressed as a fusion with the Nucleocapsid protein of Newcastle disease virus (NDV). Fusion to the carrier molecule was done to ensure that the protein construcs can serve as strong immunogens when it is tested in subsequent in vivo studies. Despite the hydrophilic properties of the VP1 peptide, as well as their carrier molecule, the recombinant proteins were expressed mostly in the insoluble fractions of bacterial lysates. The soluble form of NPt-VP1t was only around 7% of the total protein. Despite its insoluble property, moderate immunogenicity in animal studies was seen. Temperature adaptation was found to only minimally affect their solubility. In the present study, it was hypothesized that a soluble form of NPt-VP1t recombinant protein will increase its immunogenicity. Therefore, the main objective of the current study was to vaccinate the mice with the soluble fraction of the recombinant protein and evaluate the immune response produced. Following vigorous parameter testing, the NPt-VP1t was successfully produced in a soluble form. From the immunization study, this protein was found to have an increased immunogenicity in adult mice. In adult mice, the protein induced high levels of anti- VP1 IgG production. Purified VP1 antigen also stimulated activation, proliferation and differentiation of splenocytes harvested from the immunized mice. They also produced high levels of IFN-γ and IL-6 cytokines. Results obtained from this study contribute towards a better understanding of the NPt-VP1t recombinant protein as a candidate vaccine in EV71 infections.